2005
DOI: 10.1007/s11746-005-1131-0
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipases: Occurrence and production in microorganisms, assay for high‐throughput screening, and gene discovery from natural and man‐made diversity

Abstract: Various kinds of phospholipids have wide industrial applications such as in food and nutraceuticals, cosmetics, agricultural products, and pharmaceuticals. The demand for reliable biocatalysts for the production of phospholipid products, such as phospholipases A 1 , A 2 , C, and D, has steadily increased over the past several decades. A large number of microbial phospholipases have been isolated and characterized, and the increasing availability of these enzymes could eventually lead to the sustained developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 158 publications
0
15
0
1
Order By: Relevance
“…Song et al (2005) show that the water and enzyme concentration determines whether hydrolysis or esterification action of the enzyme is used. The use of a papain enzyme for a dosage higher than 4% decreased the stability of the lecithin; the decline in the hydrolysis reaction was due to lack of water content.…”
Section: Stability Of Modified Lecithinmentioning
confidence: 99%
“…Song et al (2005) show that the water and enzyme concentration determines whether hydrolysis or esterification action of the enzyme is used. The use of a papain enzyme for a dosage higher than 4% decreased the stability of the lecithin; the decline in the hydrolysis reaction was due to lack of water content.…”
Section: Stability Of Modified Lecithinmentioning
confidence: 99%
“…Phospholipases and lipases are ubiquitous enzymes obtained from a wide range of species from mammals to bacteria. Because some fine reviews provide a general overview of molecular characteristics and biological sources of the relevant enzymes (Guo et al 2005;Song et al 2005;Ramrakhiani and Chand 2011), such a description is not included in this paper.…”
Section: Enzymes Involved In Pl Modificationmentioning
confidence: 99%
“…Whichever method is used, the development of an enzyme production system is of considerable importance because the efficiency of PL synthesis highly depends on the source of enzymes. Some enzyme preparations from the animal pancreas were previously available on the market, but their high price, ill-defined composition, and limited supply have prompted researchers to find superior phospholipases from diverse natural and synthetic sources (Song et al 2005). For industrial applications, a significantly high productivity of these enzymes should be obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening organic solvent-tolerant bacteria or extremophiles has been preferred to isolate and improve naturally solvent-stable enzymes (Gupta & Khare, 2009;Doukyu & Ogino, 2010). Other protein engineering examples with industrially and/or pharmacologically important enzymes include studies on cholesterol oxidase (Pollegioni et al, 2009), cyclodextrin glucanotransferases (Leemhuis et al, 2010), human butyrylcholinesterase (Masson et al, 2009), microbial glucoamylases (Kumar & Satyanarayana, 2009), lipases of different origins (Akoh et al, 2004;Verma et al, 2008;Kurtovic et al, 2009), phospholipases (Song et al, 2005;De Maria et al, 2007;Simockova & Griac, 2009) and phytases (Rao et al, 2009). Studies on extremozymes, enzymes isolated from extremophilic species, revealed their different structural and functional characteristics which could be exploited for biotechnological applications and improved further by protein engineering (Bjarnason et al, 1993;Hough & Danson, 1999;Georlette et al, 2004).…”
Section: Applications With Various Industrially Important Enzymesmentioning
confidence: 99%